Aplicación de un proceso de mejora continua en un taller mecánico utilizando la técnica de manufactura celular - Jaramillo Caliz, Roberto Javier (2011)
The study work was carried out in a Mechanical Shop that belongs to an educational institution of half level, where you offers service of construction mechanical pieces to the industrial sector, they are also carried out practical academic. In the Shop it is observed disorder and waste, to determine them the current situation of the Shop it is analyzed by means of traveled diagram, standard times, balance loads work and other, in consequence of the study it was some waste among them those of more percentage they were: times transportation, times operations to transform the product, dissatisfaction was also observed among operators by the work load. To minimize or to eliminate these waste you implements the methodology it Manufactures Cellular the same one is a tool of lean production; with the installation it will eliminate or to reduce the times transportation, you also determines standard times of operations and a study of balance loads work to distribute works equally among operators, like part of the installation settles down two indicators to measure the advance of the process like they are: productivity and efficiency, indicators that obtained increment of 100% and 3,27% respectively after installation, this last value doesn't worry the directors of the Shop because the mechanization mechanics are used in other productions.